2017
DOI: 10.1186/s12862-017-0923-1
|View full text |Cite
|
Sign up to set email alerts
|

Human MFAP1 is a cryptic ortholog of the Saccharomyces cerevisiae Spp381 splicing factor

Abstract: BackgroundPre-mRNA splicing involves the stepwise assembly of a pre-catalytic spliceosome, followed by its catalytic activation, splicing catalysis and disassembly. Formation of the pre-catalytic spliceosomal B complex involves the incorporation of the U4/U6.U5 tri-snRNP and of a group of non-snRNP B-specific proteins. While in Saccharomyces cerevisiae the Prp38 and Snu23 proteins are recruited as components of the tri-snRNP, metazoan orthologs of Prp38 and Snu23 associate independently of the tri-snRNP as mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 56 publications
(97 reference statements)
1
19
0
1
Order By: Relevance
“…Both Gene Ontology and protein interaction database analysis of the interacting proteins revealed that ZMAT2 interacts with components of the (pre-) spliceosome (Figures 3C,D). These findings are in line with crystal structures of the budding yeast pre-spliceosome, showing that the putative ZMAT2 ortholog snu23 associates with the B* (pre-catalytic) complex (Plaschka, Lin and Nagai, 2017;Ulrich and Wahl, 2017). Our biochemical experiments identifying ZMAT2 as an interactor of the pre-spliceosome in human keratinocytes, together with our screen and validation analysis implicate RNA splicing as a potential key regulatory process in epidermal renewal and differentiation.…”
Section: Zmat2 Associates With the Pre-spliceosome In Epidermal Keratsupporting
confidence: 86%
See 2 more Smart Citations
“…Both Gene Ontology and protein interaction database analysis of the interacting proteins revealed that ZMAT2 interacts with components of the (pre-) spliceosome (Figures 3C,D). These findings are in line with crystal structures of the budding yeast pre-spliceosome, showing that the putative ZMAT2 ortholog snu23 associates with the B* (pre-catalytic) complex (Plaschka, Lin and Nagai, 2017;Ulrich and Wahl, 2017). Our biochemical experiments identifying ZMAT2 as an interactor of the pre-spliceosome in human keratinocytes, together with our screen and validation analysis implicate RNA splicing as a potential key regulatory process in epidermal renewal and differentiation.…”
Section: Zmat2 Associates With the Pre-spliceosome In Epidermal Keratsupporting
confidence: 86%
“…It is possible that ZMAT2 transiently interacts with the human spliceosome to facilitate and fine-tune these transitions. If this is the case, the timing of its association with the spliceosome might influence the efficiencies of competing splicing mechanisms, spliceosome composition or conformation (Ulrich and Wahl, 2017). Although we can only speculate about the molecular mechanisms behind our observations at this point, the combined evidence from our proteomic data and literature identified ZMAT2 as regulator of (alternative) splicing in epidermal stem cells.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Instead, splicing can be achieved by several different mechanisms using the concurrent actions of a vast number of proteins and RNAs. Large-scale network analysis suggests that enhancer proteins interact by promoting the assembly of spliceosome sub complexes, whereas silencing occurs through RNA interactions (Ulrich and 2017;Guimarães et al, 2018). The combinatorial effect of different RNA splicing regulators is shown by the results of the knock-down of the factors on inclusion of MYL6 exon.…”
Section: Discussionmentioning
confidence: 99%
“…Основная часть первичных транскриптов многоклеточных содержит более одного интрона и способна к альтернативному сплайсингу, в результате которого образуются различные мРНК из одного гена, что используется в дифференцировке клеток (Ulrich, Wahl, 2017). Поэтому количество генов, способных к альтернативному сплайсингу, возрастает при эволюционной диверсификации типов клеток в связи с усложнением программ развития (Bush et al, 2017).…”
Section: взаимосвязь сплайсинга с транспозонами и некодирующими рнкunclassified